Creation of Digital Elevated Model using lunar images of Chandrayan – 1 - Sannidhi K S; M. Z. Kurian (Institute of Advanced Engineering and Science, 2011)
The present work discusses the technique and methodology of analysing and Terrain Mapping Camera (TMC) Images acquired during India’s first Moon mission, Chandrayaan – 1, launched on October, 2008 for generating Digital Elevated Model (DEM). The Terrain Mapping Camera (TMC) on India’s first satellite for lunar exploration, Chandrayaan-1, is intended for systematic topographic mapping of the entire lunar surface, including the far side and the polar regions. A high resolution imagery of the entire Moon will help detailed study of specific lunar regions of scientific interests and further our understanding of lunar evolution. The swath of the instrument is 20 km. The digital elevation model (DEM) is a computer representation of the moon’s surface. DEMs can be generated by traditional photogrammetry based on aerial photos if they are available and they are created very often more economically by the means of space images. A Digital Terrain Model (DEM) is a continuous representation of a ground surface landform that is commonly used to produce topographic maps. DEMs are created by integrating data obtained from a wide range of techniques including remote sensing and land surveying.DEM's are sampled arrays of elevation values representing ground positions at regularly spaced intervals. Digital Elevation Model (DEM) is the terminology adopted by the USGS to describe terrain elevation data sets in a digital raster form. The normal orientation of data is by columns and rows. In this project work a DEM is created for each of the lunar images retrieved from the space craft using Triangulated Irregular Network (TIN)Key Words : Chandrayaan-1, DEM, Swath, TMC, TINDOI:http://dx.doi.org/10.11591/ijece.v1i2.80